Tatbīq Istirātījiyyāti Al-Talīm Al-Ta’āunī fī Ta’līm ‘Ilmi Al-Nahwi bi Istikhdāmi kitābi Al-Nahwi Al-Wādihi fī Ma’hadi Al-Qalami bi Al-Madrasati Al-Tsaanawiyyati Madīnati Malang - Pratama, Firman Afrian; Zamroni, Moh. Rozy; Zakiya, Zahra (Journal of Language Intelligence and Culture, 2023)
Arabic Grammar (Nahwu) has an important role in the Arabic language teaching. However, some students experience difficulties in this subject matter. This study aims to analyze the effectiveness of the Cooperative Learning strategy in learning Arabic nahwu using the Nahwu Wadhih book at Ma'had al Qalam Man 2 Malang. Further, this research was held to improve understanding and skills in Arabic both theory and practice through cooperative learning strategies. This study used experimental research designs where the data were collected through tests and questionnaires to determine the effectiveness of cooperative learning strategies in learning nahwu within Arabic language teaching. The research subject of this research were the students of Ma'had al Qalam Man 2 Malang and the board of teachers teaching nahwu subject. Based on the results of the pre-test and post-test as well as the questionnaire, it showed that the implementation of the cooperative learning strategy in learning nahwu within Arabic Language Teaching at ma'had aly MAN 2 Malang City was considered to be effective because the students achieve better score in the subject. Moreover, students were more motivated and develop high level of curiosity in learning the subject. The activity included in the learning process were group discussions, where each member of the group has a role, task and responsibility.